Chemoenzymatic Enantioselective Synthesis of the Hancock Alkaloids (S)- and (R)-Galipeine, (S)-Cuspareine, (S)-Galipinine, and (S)-Angustureine - da Cruz, Nilton Gonçalves; de Miranda, Amanda Silva; Vieira, Henriete da Silva; Kohlhoff, Markus; Mendonça, João Guilherme Pereira; Diaz, Marisa Alves Nogueira; Diaz-Muñoz, Gaspar (Synthesis, 2023)
The enantioselective synthesis of the Hancock 1,2,3,4-tetrahydroquinoline alkaloids (S)-galipeine, (S)-cuspareine, (S)-galipinine, and (S)-angustureine and the nonnatural enantiomer (R)-galipeine is described herein. The target compounds were obtained in five steps from a racemic quinaldinic acid derived α-amino ester in overall yields of 21.2% to 37.5%. The synthetic route comprised two key steps: an enzymatic kinetic resolution to control the C-2 stereocenter, affording (R)- and (S)-α-amino esters as key chiral intermediates with 94% and 72% ee, respectively, and Wittig olefination of (R)- and (S)-α-amino aldehyde synthons with the corresponding phosphonium salts using a phase-transfer system (t-BuOH/CH2Cl2), thereby allowing the introduction of alkyl substituents at C-2. Finally, the enantioselective synthesis was concluded with the catalytic hydrogenation of olefinic bonds on the Wittig adducts to furnish the target Hancock alkaloids, including (R)-galipeine, whose synthesis is described here for the first time.
Keywords: Hancock alkaloids; enzymatic kinetic resolution; Candida antarctica lipase; Wittig olefination; (R)-galipeine